Effectiveness of evidence based mental health apps on user health outcome: A systematic literature review - Yeganeh Shahsavar; Avishek Choudhury (PLoS ONE, 2025)
Research shows that over 70% of individuals globally who require mental health services lack access to adequate care. Mobile health (mHealth) technologies, such as phone apps, can be a potential solution to this issue by enabling broader and more affordable reach, thus addressing the problem of limited access to care. This study evaluates the effectiveness of evidence-based health apps on user mental health outcomes, particularly depression, anxiety, and suicidal behaviors. A comprehensive literature search was conducted using PubMed, Web of Science, and IEEE databases. In total, 6894 studies were identified, and 38 studies were selected for the review—thirty out of 38 studies employed randomized controlled trial designs. We identified 35 unique mobile apps. All the apps leveraged Cognitive Behavioral Therapy-based approaches. The most common approaches were context engagement and cognitive change, highlighting a significant focus on using personalized engagement activities and empowering users to alter their perspectives and reframe negative thoughts to improve their mental health. While mental health apps generally positively impact mental health outcomes, the findings also highlight significant variability in their effectiveness. Future studies should prioritize long-term effectiveness, wider reach to ensure it suits a diverse range of people, and the employment of objective evaluation methodologies.